2014
DOI: 10.1155/2014/919256
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers in the Management of Hypertension and/or Chronic Kidney Disease

Abstract: This minireview provides current summaries of beta-blocker use in the management of hypertension and/or chronic kidney disease. Accumulated evidence suggests that atenolol is not sufficiently effective as a primary tool to treat hypertension. The less-than-adequate effect of beta-blockers in lowering the blood pressure and on vascular protection, and the unfavorable effects of these drugs, as compared to other antihypertensive agents, on the metabolic profile have been pointed out. On the other hand, in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 55 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…Even though medications in the same antihypertensive class have similar mechanisms of action, the medications may have demonstrable differences in their ability to reduce morbidity and mortality. (24)(25)(26) Large practice data analyses would be helpful in future to examine potential advantages of certain types of medications. (25) The present study had its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Even though medications in the same antihypertensive class have similar mechanisms of action, the medications may have demonstrable differences in their ability to reduce morbidity and mortality. (24)(25)(26) Large practice data analyses would be helpful in future to examine potential advantages of certain types of medications. (25) The present study had its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…So-called "β-blockers," which are orthosteric antagonists of the receptor, are mainstays of cardiovascular medicines used to treat a wide variety of illnesses (17)(18)(19). On the other hand, β-agonists have proven very effective against asthma (20).…”
Section: Significancementioning
confidence: 99%
“…This is consistent with the relatively neutral physiologic effect of b-blockers on overall renal function. 46 Our analysis demonstrated that kidney allografts from older donors had achieved lower GFRs at the 12-month study visit and a decreased GFR relative to the baseline visit as compared with allografts from younger donors. These findings possibly reflect how aging affects the kidney by increasing glomerular, vascular, and tubular senescence resulting in decreased renal blood flow and GFR.…”
Section: Discussionmentioning
confidence: 63%
“…Our analysis did not show a difference in the effect of nebivolol and metoprolol on the renal function of kidney transplant recipients from baseline to the 12th month of the study. This is consistent with the relatively neutral physiologic effect of β‐blockers on overall renal function . Our analysis demonstrated that kidney allografts from older donors had achieved lower GFRs at the 12‐month study visit and a decreased GFR relative to the baseline visit as compared with allografts from younger donors.…”
Section: Discussionmentioning
confidence: 78%